Harnessing foreign technology to improve firm performance: Evidence from Philippine manufacturing enterprises - Raymond Gaspar (Asian Development Bank Institute (ADBI), 2022)
The paper examines the impact of foreign-licensed technology and identifies channels to effectively leverage such technology to improve the performance of manufacturing firms in the Philippines. Using the fixed effects approach to World Bank Enterprise Survey panel data for the Philippines covering 2009 and 2015, the paper finds no statistically significant impact of introducing foreign-licensed technology to manufacturing firms in terms of annual sales, employment, and energy intensity. Interestingly, the impact is more pronounced and significant among manufacturing firms that conduct workforce trainings, thereby improving absorptive capacity through better quality of labor. The empirical findings call for the Philippine government to bolster skills training and human capital formation initiatives, further incentivizing in-house training, to support the advancement of local absorptive capacity and better assimilate the use of foreign technologies.
Keywords: L24; L25; L60; 330; technology transfer; technology licensing; firm performance; local absorptive capacity; Philippines